2007
DOI: 10.1038/sj.bmt.1705664
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden in patients undergoing autologous stem-cell transplantation

Abstract: Patients who undergo autologous peripheral blood stem cell (PBSC) transplantation experience multiple symptoms that adversely affect quality of life. We assessed symptoms during the acute phase of autologous PBSC transplantation to determine the severity of individual symptoms and to determine overall symptom profiles in 100 patients with multiple myeloma or non-Hodgkin's lymphoma. Study subjects completed the blood and marrow transplantation module of the M. D. Anderson Symptom Inventory before hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
105
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 31 publications
13
105
1
2
Order By: Relevance
“…At the time of hospital discharge, the average severity of sleep disruption among allogeneic and autologous patients was still moderately elevated relative to baseline symptomatology (i.e., .51 SD) (26). Nevertheless, it appears that increases in sleep disruption are generally transient; by day 100, sleep disruption returns to levels comparable to pre-HCT (4, 25, 31), although these levels are substantially elevated even before the transplant. Patients receiving allogeneic HCT demonstrate similar levels of sleep disruption near day 100 to patients receiving autologous transplant (4).…”
Section: Sleep Disruption and Disorders During The Acute Transplant Pmentioning
confidence: 97%
See 3 more Smart Citations
“…At the time of hospital discharge, the average severity of sleep disruption among allogeneic and autologous patients was still moderately elevated relative to baseline symptomatology (i.e., .51 SD) (26). Nevertheless, it appears that increases in sleep disruption are generally transient; by day 100, sleep disruption returns to levels comparable to pre-HCT (4, 25, 31), although these levels are substantially elevated even before the transplant. Patients receiving allogeneic HCT demonstrate similar levels of sleep disruption near day 100 to patients receiving autologous transplant (4).…”
Section: Sleep Disruption and Disorders During The Acute Transplant Pmentioning
confidence: 97%
“…Of these, 9 studies did not provide estimates of prevalence of sleep disruption or comparisons to individuals not receiving HCT (7, 23-30). The remaining 7 studies are heterogeneous in terms of their sample composition, sample size, measure of sleep, and clinical cutoff (3, 4, 31-35). Thus, it is not surprising that there is substantial heterogeneity among study findings.…”
Section: Sleep Disruption and Disorders Prior To Transplantmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Campagnaro et al 11 used the M. D. Anderson Symptom Inventory (MDASI), and Anderson et al 10 used the MDASI Blood and Marrow Transplantation (MDASI-BMT) module. Both studies found that symptoms intensified throughout transplantation and decreased by Day 30.…”
Section: Introductionmentioning
confidence: 99%